Optimal reactive strength index: Is it an accurate variable to optimize plyometric training effects on measures of physical fitness in young soccer players? - Ramirez-Campillo, R.; Alvarez, C.; Garcia-Pinillos, F.; Sanchez-Sanchez, J.; Yanci, J.; Castillo, D.; Loturco, I.; Chaabene, H.; Moran, J.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2018)
This study aimed to compare the effects of drop-jump training using a fixed drop-box height (i.e., 30-cm [FIXED]) vs. an optimal (OPT) drop-box height (i.e., 10-cm to 40-cm: generating an OPT reactive strength index [RSI]) in youth soccer players' physical fitness. Athletes were randomly allocated to a control group (n = 24; age = 13.7 years), a fixed drop-box height group (FIXED, n = 25; age = 13.9 years), or an OPT drop-box height group (OPT, n = 24; age = 13.1 years). Before and after 7 weeks of training, tests for the assessment of jumping (countermovement jump [CMJ], 5 multiple bounds), speed (20-m sprint time), change of direction ability (CODA [Illinois test]), strength {RSI and 5 maximal squat repetition test (5 repetition maximum [RM])}, endurance (2.4-km time trial), and kicking ability (maximal kicking distance) were undertaken. Analyses revealed main effects of time for all dependent variables (p < 0.001, d = 0.24-0.72), except for 20-m sprint time. Analyses also revealed group × time interactions for CMJ (p < 0.001, d = 0.51), depth jump (DJ) (p < 0.001, d = 0.30), 20-m sprint time (p < 0.001, d = 0.25), CODA (p < 0.001, d = 0.22), and 5RM (p < 0.01, d = 0.16). Post hoc analyses revealed increases for the FIXED group (CMJ: 7.4%, d = 0.36; DJ: 19.2%, d = 0.49; CODA: -3.1%, d = -0.21; 5RM: 10.5%, d = 0.32) and the OPT group (CMJ: 16.7%, d = 0.76; DJ: 36.1%, d = 0.79; CODA: -4.4%, d = -0.34; 5RM: 18.1%, d = 0.47). Post hoc analyses also revealed increases for the OPT group in 20-m sprint time (-3.7%, d = 0.27). Therefore, to maximize the effects of plyometric training, an OPT approach is recommended. However, using adequate fixed drop-box heights may provide a rational and practical alternative.